Feminism, Popular Feminism, and (Feminist) Popular Culture (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This paper aspires to explore the connection between feminism and popular culture through the lens of key ideas presented in three books that deal with it – Feminism and Pop Culture, We Were Feminists Once (From Riot Grrrl to Cover Girl®, The Buying and Selling of a Political Movement) by Andy Zeisler, and Cosmopolitics by Maša Grdešić. Both authors emphasize the importance of approaching popular culture from a feminist angle in the context of contemporary consumer society, and the need for feminist intervention in existing forms of popular culture. Accordingly, the focus of the analysis is put on the interplay between feminism and various forms of popular culture and its practices. Apart from providing a historical overview of the development of relationship between popular culture and feminism, this paper also deals with various forms of feminism that emerged under the auspices of third-wave feminism and that work in favour of the capitalist demands of modern times – marketplace feminism, feminism of choice, and celebrity feminism. These hybrid forms of feminism illustrate only too well the commodification of feminism and the appropriation of feminist vocabulary as also topics of this study.
Keywords: феминизам; трећи талас феминизма; постфеминизам; тржишни феминизам; популарна култура; женски часописи